Analisis Pemahaman Ayat-Ayat Toleransi dalam Penguatan Moderasi Beragama pada Generasi Z - Miladur Rizki; Idris Siregar (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This article examines how Generation Z students at the Faculty of Ushuluddin and Islamic Studies and the Faculty of Sharia and Law, State Islamic University of North Sumatra, understand Qur’anic verses on tolerance as a foundation for religious moderation, how that understanding is implemented in daily practice, and the factors shaping it. Employing a descriptive-analytical qualitative approach with in-depth interviews, participatory observation, and documentation study, the data are analyzed through the Miles and Huberman interactive model and thematic analysis. The theoretical review shows that the Ministry of Religious Affairs’ concept of religious moderation, covering national commitment, tolerance, non-violence, and accommodation of local culture, closely relates to the messages of tolerance found in QS. Al-Kafirun: 1-6, QS. Al-Baqarah: 256, QS. Al-Hujurat: 13, QS. Yunus: 99, and QS. Al-An’am: 108. A synthesis of comparable prior studies suggests that Generation Z students’ understanding tends to be textual-normative in early semesters and gradually becomes more contextual as exposure to tafsir courses, cross-faith student organizations, and healthy digital literacy increases. Social media emerges as a double-edged instrument that both broadens access to religious knowledge and risks spreading exclusive narratives absent critical literacy. The article recommends strengthening curriculum integration on religious moderation, optimizing student organizations, and providing digital religious-literacy mentoring for Generation Z students at Islamic higher education institutions